Cartografias da biogeofísica na Amazônia: Comunicação, Controvérsias e Redes da Tecnociência do Clima e Meio Ambiente - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
The phenomena of misinformation on the internet challenge the dissemination of scientific knowledge, especially climate and environmental studies in the Amazon. In this scenario, teaching and research institutions and their respective projects face the need to create knowledge management strategies to communicate and popularize results. Thus, in this thesis, a cartography of the controversies of biogeophysics in the Amazon region is presented, developed from the experience and communicational intervention at the Atmospheric Physics and Chemistry Laboratory of the Federal University of Western Pará (Ufopa), where the research group in Biogeophysics of the Amazon Region and Environmental Modeling (Brama) works together with a national and international collaboration network. The objective was to carry out a quantitative and qualitative analysis of this socio-technical network. In Chapter 3, transmethodological procedures, based on the Actor-Network Theory (ANT), such as photographic and audiovisual recording; conceptual modeling; computational ontology in Protegé; creation of social networks and websites; monitoring cold and hot controversies about the environment in digital media; construction of the timeline of experience and controversies; interviews and transcription; writing of field trials/reports – were described. It is concluded that conceptual modeling and computational ontology, by representing and formalizing an observed environment, can contribute to the management and communication of scientific knowledge. However, they, not least isolated institutional marketing and journalism, may be the only strategies to be used to popularize scientific knowledge, in the face of scientific denialism and colonialism; of data and the intense processes of social datafication.
Keywords: Clima e Meio Ambiente; Comunicação; Teoria Ator-Rede; Modelagem Conceitual; Ontologia; CNPQ:: GEOCIÊNCIAS; SOCIEDADE, NATUREZA E DESENVOLVIMENTO